Sites of Aboriginal Difference: A Perspective on Installation Art in Canada - Collins, Curtis J (2002)
"This dissertation traces the presence of installation-based practices among artists of Aboriginal ancestry via selected exhibitions across Canada. It begins with a methodological perspective on Canadian art history, federal law, and human science, as a means of establishing a contextual backdrop for the art under consideration. The rise of an Indian empowerment movement during the twentieth century is then shown to take on an international voice which had cultural ramifications at the 1967 Canadian International and Universal Exhibition. Nascent signs of a multi-mediatic aesthetic are distinguished in selected works in Canadian Indian Art '74, as well as through Native-run visual arts programs. First Nations art history is charted via new Canadian art narratives starting in the early 1970s, followed by the development of spatial productions and hybrid discourses in New Work By a New Generation in 1982, and Stardusters in 1986. The final chapter opens with a history of installation art since the Second World War, as related to the pronounced presence of multi-mediactic works in Beyond History in 1989. Post-colonial and postmodern theories are deployed to conclusively situate both the artistic and political concerns featured throughout this study, and lead into the analysis of selected installations at Indigena: Contemporary Native Perspectives and Land, Spirit, Power: First Nations at the National Gallery of Canada. These 1992 shows in the national capital region ultimately confirm the maturation of a particular socio-political aesthetic that tested issues of Canadian identity, while signifying Aboriginal sites of difference."--
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé